STUDENTS’ PERCEPTION OF THE USE OF STORYTELLING TECHNIQUE TO IMPROVE VOCABULARY SKILL - Wahyu Trimastuti (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2018)
The main objective of the research is to find out whether story telling technique can improve vocabulary skill or not. The descriptive quantitative method was employed in this research. The samples of the research were business management of MBIS-W41/15 which consists of twenty one students. To collect the data, the writer used questionnaire to know the students’ perception with storytelling technique and vocabulary test to know whether the final test score of the students have a significant progress or not. Storytelling technique deliver a good method to support,moyivate, and encourage knowledge. It can be seen that students were encouraged to be actively and motivately in learning process. Based on the reserach finding, it can be conclude that storytelling technique can improve vocabulary skill and give good atmosphere in teaching learning process. Using storytelling students more interesting and understanding new words. They can work together and share idea to encourage new knowledge which discuss in topic of their lesson. It is good applying  story telling to improve students’ vocabulary